Exploiting reductive evolution in Mycobacterium ulcerans to develop a single-dose cure for Buruli ulcer - Sangeeta, Susan Thomas (Nanyang Technological University, 2021)
Summary Mycobacteria form one of the most successful human pathogens, with Mycobacterium tuberculosis causing tuberculosis and Mycobacterium leprae causing leprosy. Following the effective implementation of the BCG vaccine and the rigorous and conscious effort taken globally to curb tuberculosis and leprosy, infections due to non-tuberculous mycobacteria (NTM) are now gaining prominence worldwide. Some of the predominant NTM infections include the skin ulcers caused by Mycobacterium ulcerans and lung infections due to Mycobacterium abscessus and Mycobacterium avium complex (MAC) agents. Buruli ulcer, a slowly progressing ulcerative disease of the skin caused by M. ulcerans, is the third most common mycobacterial disease. The disease affects mainly children in regions of West Africa and now is seeing a resurgence in regions of South-East Australia. For several years, the disease was considered a neglected tropical disease, and a suboptimal treatment regimen comprising of daily oral rifampicin and streptomycin injections over 8 weeks has hindered effective control of the disease. Moreover, drug toxicity issues such as ototoxicity and renal failure make the treatment regimen very difficult to follow through for the patients. On consideration of drug repurposed for NTM from the drug pipeline for M. tuberculosis, Q203 (Telacebec) was found to be an ideal drug candidate for M. ulcerans. Q203 is a clinical-stage drug candidate for M. tuberculosis that targets the respiratory cytochrome bcc:aa3, a terminal electron acceptor in the critical oxidative phosphorylation (OxPhos) pathway. In silico studies have shown that the Q203 binding site (QcrB domain of the cytochrome bcc:aa3) was conserved in both M. tuberculosis and M. ulcerans. However, in M. tuberculosis, Q203 is rendered bacteriostatic due to the rescue action of the alternate terminal oxidase, cytochrome bd oxidase. Contrarily, M. ulcerans lacks a functional cytochrome bd oxidase due to a non-sense mutation as part of drastic genome downsizing in its evolutionary diversification from Mycobacterium marinum. Hence, M. ulcerans is solely dependent on cytochrome bcc:aa3 as a terminal electron acceptor, and in this scenario Q203 might be an exceptionally fitting drug candidate for M. ulcerans. In this study, the cytochrome bd oxidase of M. ulcerans was confirmed to be inactive using a methylene blue-based functional assay. M. ulcerans was found to be hyper susceptible to Q203 with potency in sub-nanomolar ranges (MIC50: 0.2-0.9 nM) as opposed to M. tuberculosis where MIC50 of Q203 was 1.5-2.8 nM. The drastic reduction in both ATP levels and Oxygen Consumption Rate on exposure to Q203 validated the action of the drug on the OxPhos pathway. A first attempt at raising drug resistant mutants in M. ulcerans in the laboratory was successful in this study. Low resistance rates (5.6 x 10-9) to Q203 was demonstrated for M. ulcerans and all the resistant isolates had mutations mapped to the qcrB gene. Previously, in vivo studies have shown remarkable sterilising action of Q203 on M. ulcerans in the foot-pad infection model in mice compared to the current clinical standards of rifampicin and streptomycin. In our study, we were able to validate the use of a single dose of Q203 to completely clear infection in the mouse foot-pad infection model. Marked oedema and histopathological evidence of disease were significantly reduced with Q203 treatment alone. In conclusion, the reductive evolution of M. ulcerans has driven the organism to hypersusceptibility to Q203 due to an exclusive dependence of the organism on one terminal electron acceptor in the quintessential OxPhos pathway. This was successfully translated to achieve a single dose cure in the Buruli ulcer mouse model of infection with no relapse.